1971
DOI: 10.1111/j.1471-4159.1971.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Transamination of Amino Acids in Homogenates of Rat Brain

Abstract: Abstract— The aminotransferase activity of homogenates of brains from adult and neonatal rats has been investigated. Aminotransferase activity was demonstrated wtih 15 of 22 amino acids incubated with seven keto acids. The basic amino acids exhibited little or no activity. The greatest activity was obtained when glutamate or aspartate was incubated with α‐ketoglutarate or oxaloacetate. Significant activity was also observed when the neutral aliphatic and aromatic amino acids were incubated with these two ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 37 publications
3
23
2
Order By: Relevance
“…For both aspartate and alanine intracellular 15 N-labeling is 40% to 50% in the co-cultures demonstrating the relevance of both transamination reactions. Even though this is in contrast to findings of relatively low activity of ALAT compared with AAT in homogenates of rat brain, 34 a cell culture study found that ALAT activity is cell-type specific with a three-fold higher enzyme activity in astrocytes compared with neurons. 35 Since aspartate is not released from healthy astrocytes owing to glutamate transporters generating a large inward gradient of glutamate as well as aspartate, 36 this amino acid cannot be considered an alternative ammonia scavenger.…”
Section: Nhcontrasting
confidence: 86%
“…For both aspartate and alanine intracellular 15 N-labeling is 40% to 50% in the co-cultures demonstrating the relevance of both transamination reactions. Even though this is in contrast to findings of relatively low activity of ALAT compared with AAT in homogenates of rat brain, 34 a cell culture study found that ALAT activity is cell-type specific with a three-fold higher enzyme activity in astrocytes compared with neurons. 35 Since aspartate is not released from healthy astrocytes owing to glutamate transporters generating a large inward gradient of glutamate as well as aspartate, 36 this amino acid cannot be considered an alternative ammonia scavenger.…”
Section: Nhcontrasting
confidence: 86%
“…No significant signal change in alanine C2 signal at 50.1 ppm was observed in either the bicuculline-treated or the glioma rats upon saturation of pyruvate C2 at 207.9 ppm during [2-13 C]glucose infusion (data not shown). The difficulty of detecting the saturation transfer effect catalyzed by alanine aminotransferase (EC 2.6.1.2) should be due to the intrinsic low activity of alanine aminotransferase in brain tissue in both alanine 3 pyruvate and pyruvate 3 alanine directions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Cancellation of the elevated Ala signal at 1.47 ppm in the difference spectrum was incomplete due to partial saturation of the Ala C3 signal at 16.8 ppm during the control experiment with the irradiation frequency placed at 12.4 ppm. Note that the rate of alanine aminotransferase reaction is too low in brain tissue to generate any detectable magnetization transfer effect in vivo as explained earlier [2,28]. Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The relative standard deviations of the reported percent change are in agreement with the predicted values using eq. [28] given by Alger and Shulman [29].…”
Section: Resultsmentioning
confidence: 99%